[papers] : 17th International association of historians of Asia (IAHA) conference, 18-22 December 2002, Dhaka, Bangladesh - International Association of Historians of Asia (IAHA) Conference 2002 : Dhaka) ([S.l : s.n], 2002)
AHA Conference ; speeches and abstracts of papers
Seminar ini mengandungi 22 kertas kerja
In English
Keywords: Asia -- History -- Congresses